A mathematical solution for mixed convection MHD casson fluid passing through an infinite inclined plate - Nur Fatihah, Mod Omar; Zulkhibri, Ismail; Rahimah, Jusoh; Husna Izzati, Osman; Ahmad Qushairi, Mohamad ((IGSES) Kyushu University, 2025)
The mixed convection through an infinitely inclined plate of magnetohydrodynamic (MHD) Casson fluid flowhas been conducted in this research. To investigate the influence of temperature, concentration, and velocity, theLaplace transform method has been employed in this research. This approach enables the analytical solution of thegoverning equations. The effect of key dimensionless parameters, namely Casson fluid parameter, inclination angle, magnetic parameter and time towards velocity, concentration, and temperature profiles, is presented through graphicalrepresentations supported by numerical data.